2023
DOI: 10.3390/polym15122629
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propolis Impregnation on Polylactic Acid (PLA) Scaffolds Loaded with Wollastonite Particles against Staphylococcus aureus, Staphylococcus epidermidis, and Their Coculture for Potential Medical Devices

Ana Isabel Moreno,
Yeison Orozco,
Sebastián Ocampo
et al.

Abstract: Several diseases and injuries cause irreversible damage to bone tissues, which may require partial or total regeneration or replacement. Tissue engineering suggests developing substitutes that may contribute to the repair or regeneration process by using three-dimensional lattices (scaffolds) to create functional bone tissues. Herein, scaffolds comprising polylactic acid and wollastonite particles enriched with propolis extracts from the Arauca region of Colombia were developed as gyroid triply periodic minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 91 publications
(110 reference statements)
0
13
0
Order By: Relevance
“…The antimicrobial activity of propolis has been largely attributed to the presence of organic compounds such as phenols, flavonoids, flavanones, and terpenes, among others [ 63 , 64 ]. The propolis used in this study showed the presence of phenolic compounds and flavonoids, indicating that these may influence the antimicrobial activity found against the evaluated species [ 65 ]. Propolis is characterized by its varied and complex composition, which allows it to affect bacterial species through mechanisms that include damage to the bacterial cell membrane [ 66 ], inhibition of bacterial enzymatic activity [ 67 ], induction of oxidative stress [ 68 ], and modulation of virulence factors [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial activity of propolis has been largely attributed to the presence of organic compounds such as phenols, flavonoids, flavanones, and terpenes, among others [ 63 , 64 ]. The propolis used in this study showed the presence of phenolic compounds and flavonoids, indicating that these may influence the antimicrobial activity found against the evaluated species [ 65 ]. Propolis is characterized by its varied and complex composition, which allows it to affect bacterial species through mechanisms that include damage to the bacterial cell membrane [ 66 ], inhibition of bacterial enzymatic activity [ 67 ], induction of oxidative stress [ 68 ], and modulation of virulence factors [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our activity values align with other studies, which have reported antioxidant activity against the DPPH free radical ranging from 17% to 70% and against the ABTS free radical ranging from 5% to 28% ( Ahn et al, 2007 ). This antioxidant activity can be attributed to the presence of specific components such as phenols and flavonoids found in propolis from this region ( Moreno et al, 2023 ). Furthermore, the antioxidant activity, along with the presence of phenolic compounds and flavonoids, may be associated with antimicrobial activity.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an increasing focus on human dental MSCs, classified based on their niche within the dental environment ( Machado et al, 2012 ). In the context of regenerative dentistry, scaffolds have been extensively studied in vitro and in vivo , with an emphasis on factors such as scale (micro, nanometric, or hyper-hierarchical), origin (natural or synthetic), product type (massive or customized), manufacturing techniques (including 3D printing and bioprinting) ( Nikolova and Chavali, 2019 ), functionality (3D, 3D functionalized, and 4D) ( Soleymani and Naghib, 2023 ; Wan et al, 2023 ), geometries (periodic or non-periodic) and composition (polymer, metallic, or ceramic) ( Teixeira et al, 2009 ; Higuita-Castro et al, 2012 ; Martin et al, 2019 ; Moreno et al, 2023 ). However, ceramic-based 3D scaffolds have received relatively less attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite initial viability reduction, hDPSCs thrived by the seventh day. These results suggest that these novel scaffolds could be promising as bone substitutes capable of controlling typical severe infectious processes [ 45 ]. The possibility of prototyping with both ABS and PLA polymers allows the manufacture of scaffolds with complex geometries, both internal and external, which allows the production of infinite forms for patient care (Sears et al, 2016).…”
Section: Discussionmentioning
confidence: 99%